2007
DOI: 10.1099/vir.0.82634-0
|View full text |Cite
|
Sign up to set email alerts
|

PDTC inhibits picornavirus polyprotein processing and RNA replication by transporting zinc ions into cells

Abstract: Previously, it was shown that pyrrolidine dithiocarbamate (PDTC) inhibits proteolytic polyprotein processing and replication of human rhinovirus by transporting metal ions into cells. Here, it is shown that PDTC also inhibits replication of two other picornaviruses: coxsackievirus B3 (CVB3), a closely related virus that belongs to the genus Enterovirus, and mengovirus, an encephalomyocarditis virus strain that belongs to the genus Cardiovirus, and that this inhibition is due to the dithiocarbamate moiety of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 53 publications
4
84
0
Order By: Relevance
“…Five hours p.i., cells were starved half an hour prior to 1 h of labeling with [ 35 S]Met/Cys. After labeling, cells were lysed, and cellular extracts were subjected to immunoprecipitation using either antibodies specific for 3D or 3C (kindly provided by C. Cameron, Pennsylvania State University) as described previously (22). Then, the protein pattern was analyzed by SDS-PAGE and autoradiography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five hours p.i., cells were starved half an hour prior to 1 h of labeling with [ 35 S]Met/Cys. After labeling, cells were lysed, and cellular extracts were subjected to immunoprecipitation using either antibodies specific for 3D or 3C (kindly provided by C. Cameron, Pennsylvania State University) as described previously (22). Then, the protein pattern was analyzed by SDS-PAGE and autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we have demonstrated that PDTC has negative effects on picornavirus replication by influencing the processing of the viral polyprotein (21,22).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Calpain inhibitors inhibit the replication of echovirus 1, possibly by targeting the activities of calpain 1 and 2 (Upla et al, 2008). Pyrrolidine dithiocarbamate (PDTC) inhibits polyprotein processing of entero-and cardioviruses by transporting zinc ions into the cells with different mechanisms depending on the virus species (Krenn et al, 2005;Lanke et al, 2007). For PDTC, a mechanism via the ubiquitin-proteasome pathway is also proposed for the inhibitory effect on coxsackievirus B3 (CVB3) infection (Si et al, 2005).…”
Section: Introductionmentioning
confidence: 99%